In utero and lactational exposure to triclocarban: reproductive effects on female rat offspring - Costa, Nathalia Orlandini; Borges, Lorena Ireno; Cavalcanti, Liara Freitas; Montagnini, Bruno Garcia; Anselmo Franci, Janete Aparecida; Kiss, Ana Carolina Inhasz [UNESP]; Gerardin, Daniela Cristina Ceccatto (Wiley-Blackwell, 2019)
Triclocarban (TCC) is an antimicrobial compound widely used in personal care products such as soaps, toothpaste, and shampoo. This agent is incompletely removed by wastewater treatment and represents an environmental contaminant. Recent studies have shown that TCC is associated with some endocrine disruptions. The aim of the present study was to evaluate if TCC exposure during critical periods of development (gestation and lactation) could lead to adverse effects on reproductive and behavior parameters of female offspring. Pregnant female Wistar rats were divided into four groups (n = 8-11/group): Control; TCC 0.3 mg/kg (TCC 0.3); TCC 1.5 mg/kg; TCC 3.0 mg/kg (TCC 3.0); and treated daily by oral gavage from gestational day 0 to lactational day 21. The female pups (F1 generation) were weaned on post-natal day 21 and included in the study. No litter-mates were used for the same group. There was a decrease in estradiol levels in the TCC 0.3 and TCC 3.0 groups. Moreover, there was a decrease in progesterone levels and an increase in pre-implantation loss in the TCC 3.0 group in adulthood. It is suggested, in this study, that the decrease in progesterone biosynthesis could interfere with implantation process. The exposure window to TCC is an important factor, as we found alterations only in the offspring.
Keywords: behavior; endocrine disruptor; fertility; maternal exposure; progesterone